Heinrich Heine : a modern biography - Sammons, Jeffrey L. (Princeton University Press, 1979)
Heinrich Heine has been one of the liveliest topics in German literary studies for the past fifteen years. His life was marked by an exceptionally high pitch of constant public controversy and an extraordinary quantity of legend and speculation surround his reputation. This biography, the first in English in over twenty years and the first fully documented one in over a century, makes full use of the newest material in contemporary studies as well as of older scholarship. Originally published in 1980. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.